2019
DOI: 10.1111/jabr.12158
|View full text |Cite
|
Sign up to set email alerts
|

Social comparisons, social media addiction, and social interaction: An examination of specific social media behaviors related to major depressive disorder in a millennial population

Abstract: Although studies have shown that increases in the frequency of social media use may be associated with increases in depressive symptoms of individuals with depression, the current study aimed to identify specific social media behaviors related to major depressive disorder (MDD). Millennials (N = 504) who actively use Facebook, Twitter, Instagram, and/or Snapchat participated in an online survey assessing major depression and specific social media behaviors. Univariate and multivariate analyses were conducted t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
43
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 66 publications
(52 citation statements)
references
References 30 publications
(36 reference statements)
7
43
1
1
Order By: Relevance
“…Previous research has suggested that comparing oneself to others on social media may negatively impact one's psychological well-being (Liu et al, 2017;Robinson et al, 2019). The results of the current study support this finding.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Previous research has suggested that comparing oneself to others on social media may negatively impact one's psychological well-being (Liu et al, 2017;Robinson et al, 2019). The results of the current study support this finding.…”
Section: Discussionsupporting
confidence: 86%
“…These two specific behaviors included upward social comparison and posting while drinking alcohol. Previous research suggests increasing social interaction, whether face-to-face or online, may buffer psychological distress symptoms (Robinson et al, 2019). However, social media use may also increase anxiety for some people (Andreassen et al, 2016;Primack et al, 2016;Vannucci et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Yet despite the public's awareness of social media addiction, academic research remains limited. Only recently have scholars demonstrated that individuals with major depressive disorder report significantly higher social media addiction scores (Robinson et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…The experiment of Hunt, Marx, Lipson, and Young [33] revealed that FOMO and its associated depression can be reduced by limiting the use of social media. Robinson, Bonnette, Howard, Ceballos, Dailey, Lu, and Grimes [34] explained the relationship between Internet addiction and depression in more detail based on a comprehensive survey. They found that Major Depressive Disorder was more likely to be found among people who had a stronger tendency to compare themselves with other people on social media, who were more eager to maintain a positive image on social media, and had a larger perceived discrepancy between their online and offline identity.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…People can feel the need to keep updated about the event in order to feel involved in the group alongside their peers. Referring to the observation of Robinson et al [34], Internet addiction in the context of a movement can lead to depression due to comparison between users and their peers who are highly involved in the movement and adjusting one's persona on social media to fit the movement atmosphere. Third, a movement context itself can be emotionally provoking.…”
Section: Theoretical Frameworkmentioning
confidence: 99%